The regulatory role of ZmSTOMAGEN1/2 in maize stomatal development is elucidated via gene editing and metabolic profiling. - Juan-Juan Xu; Qing-Yun Chen; Li-Fang Qin; Yuan Liu; You-Zhi Li; Xian-Wei Fan (PLoS ONE)
Stomatal development is mediated by EPIDERMAL PATTERNING FACTORs (EPFs), a family of secreted peptides including STOMAGEN/EPFL9 in Arabidopsis. To clarify the functional role of STOMAGEN orthologues in maize (Zea mays), we generated a double knockout mutant of ZmSTOMAGEN1 and ZmSTOMAGEN2 using CRISPR/Cas9 system. Comprehensive phenotypic analysis revealed that the zmstomagen1/2 mutant exhibited severe stomatal development defects, including complete absence of stomata between epidermal cells in stomatal lineage files and abnormal stomatal complexes with small lobed cells. These aberrant cells likely arose from failed asymmetric divisions of guard mother cells, ultimately preventing the formation of functional stomatal complexes. A double knockout of ZmSTOMAGEN1/2 reduced the expression of SPEECHLESS1 (SPCH1), MUTE, SCREAM2 (SCRM2), and STOMATAL DENSITY AND DISTRIBUTION1 (SDD1), impairing stomatal initiation and cell fate transition in early stomatal lineage cells. The mutant displayed a lower stomatal density and index, leading to reduced net photosynthetic rate, transpiration rate, and stomatal conductance but increased water-use efficiency (WUE). Compared to the wild-type plants (HiII-A × HiII-B), the zmstomagen1/2 mutant exhibited significant alterations in phytohormone homeostasis. These included brassinosteroid metabolite imbalance (increased typhasterol, decreased castasterone) and differential gibberellin regulation (elevated GA4, reduced GA1). These hormonal perturbations suggest that impaired stomatal morphogenesis in zmstomagen1/2 mutants result from disrupted crosstalk between multiple hormonals signaling networks. Our findings reveal a crucial role for ZmSTOMAGEN1/2 in regulating cell fate decisions within the stomatal lineage and provide a potential strategy for enhancing WUE in maize by manipulating ZmSTOMAGEN1/2 expression.